Analisis Diksi pada Headline Berita Politik Portal Berita Liputan6 - Mahmudah Widya Damayanti; Dasa Oktaviani; Wahyunengsih (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Information about the development of the political situation in Indonesia is one of the favorite readings for the public. Therefore, it is important to discuss how online news changes the title of the news because it greatly influences the perception of society at large. This study aims to analyze the use of political news diction on the online news portal Liputan6.com. In addition, it also describes the use of connotations and denotations contained in political news headlines on the news portal Liputan6.com. This research is classified as descriptive qualitative. The data analysis technique used is analytical-descriptive technique. In this study, there is the use of diction in the form of 7 connotative dictions, 1 denotative diction and 1 synonym. The use of diction in news portal Liputan6.com is often not directly related to news content.